IFNγ augments TKI efficacy by alleviating protein unfolding stress to promote GSDME-mediated pyroptosis in hepatocellular carcinoma - Xiaoxiao Li; Fujia Lu; Jie Zhou; Xiong Li; Yan Li; Weijie Ye; Jing Li; Liguo Yang; Shi Tang; Yuhan Zhou; Songlin Yin; Yuan Gao; et al. (Cell Death and Disease)
Abstract Tyrosine kinase inhibitors (TKIs) are the standard treatment for advanced hepatocellular carcinoma (HCC). However, their therapeutic efficacy is often limited by drug resistance, primarily driven by tumoral intrinsic mechanisms. In this study, we demonstrate that IFNγ in the tumor microenvironment can potentiate TKI response, and that ablation of IFNγ receptor on HCC cells leads to TKI resistance in vivo. Mechanistically, IFNγ synergizes with TKI to induce GSDME-mediated pyroptosis of HCC cells. The PERK-mediated unfolded protein response (UPR) protects HCC cells from TKI-induced pyroptosis. IFNγ attenuates PERK activation by inducing the expression of PDIA1, which alleviates the stress of protein unfolding. In vivo, PERK inhibition augments TKI therapy, and elevated PERK expression correlates with poor overall survival of patients with HCC. Moreover, IFNγ-producing CD8+ T cells can potentiate TKI efficacy. Combining PD-1 blockade to activate T-cell response with TKI therapy synergistically suppresses the growth of GSDME-expressing HCC tumors, which is further enhanced by the PERK inhibitor. Our findings reveal how IFNγ signaling modulates TKI response and demonstrate the potential of a sequential combination of ICB-mediated immunotherapy and TKI therapy for patients with GSDME+ HCC. T cell-derived IFNγ enhances TKI-induced pyroptosis in HCC. Mechanistic illustration of IFNγ secreted from CD8+ T cells enhancing TKI-induced GSDME-mediated pyroptosis in hepatocellular carcinoma via suppression of the PERK pathway. Created with BioRender.com.